Handbook of research on social, economic, and environmental sustainability in the development of smart cities - Vesco, Andrea, 1978-; Ferrero, Francesco, 1975- (Information Science Reference, an imprint of IGI Global, 2015)
"This book brings together the necessary research and interdisciplinary discussion to address dilemmas created by population growth and the expansion of urban environments for those interested in the urban planning and technological advancements necessary for the creation of smart cities"-- Provided by publisher.
Keywords: City planning.; City planning -- Technological innovations.; Urbanization.; Technological innovations.; Sustainability.; elektronické knihy; electronic books